THE EFFECT OF ITRAINING ON EMPLOYEE PERFORMANCE AT THE BINA MARGA CIPTA KARYA TATA RUANG PERTAHANAN DAN PERUMAHA RAKYAT KABUPATEN SIDENRENG RAPPANG - Padel; Haeril Haeril; Muhammad Taufiq (Universitas Ichsan Sidenreng Rappang, 2024)
MuhammadFadly ES1220090 2024. The Effect of iTraining on Employee Performance at the Bina Marga Cipta Karya Tata Ruang Pertahanan dan Perumaha Rakyat Kabupaten Sidenreng Rappang. This study aims to determine whether there is an effect between training on employee performance at the Department of Public Works, Public Works, Spatial Planning, Land and Public Housing of Sidenreng Rappang Regency. The population in this study were all employees at the Department of Public Works, Public Works, Spatial Planning, Land and Public Housing of Sidenreng Rappang Regency, totaling 39 people, and the sampling technique used was saturated sampling. Data were obtained from primary data and secondary data, data collection techniques used were observation, questionnaires and documentation, the method used in this study was a quantitative research method. Keywords: Training, Employee Performance